Histological Study of Common House Gecko (Hemidactylus frenatus) Regenerated Tail - Rakhmiyati Rakhmiyati; Muhammad Jafar Luthfi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2016)
Common house gecko (Hemidactylus frenatus) belongs to suborder Lacertilia that has capacity to shed its tail (autotomy) as a self-defense mechanism. After autotomy, tail regeneration occurs. Axiale skeleton of an original tail is composed of bony vertebrae, whereas the the regenerate one is comprised of cartilaginous tube. The purpose of this study was to determine the histological difference between axial skeleton of the original tail and the regenerate one of the common house gecko. Twenty four individuals consist of twelve common house gecko with original tail and twelve with regenerate tail were used. Microanatomical observations were carried on histological slide of original and regenerated tail stained with Hematoxylin-Eosin and Mallory Acid Fuchsin. The results showed that the original tail comprised of bony vertebrae whereas regenerated tail supported by cartilaginous tube.